Getting ready for the marriage market?: A rejoinder - Grimps, Florian; Schneider, Björn (Journal of biosocial science, 2012)
There is an obvious need for better understanding of people's motives for body weight change, due to the importance of the health-related, social and economic consequences of obesity. In particular, exploration of little-discussed social aspects could provide further insights, but requires, however, close examination. This also applies to the study of the effect of marriage-market-related incentives and divorce risks on individual body mass index (BMI). Nevertheless, the ongoing debate about whether and to what extent the risk of divorce influences the body constitution of middle-aged individuals has as yet failed to mature into a common agreement. This paper will therefore re-examine theoretical assumptions and statistical calculations to clarify still contentious points. Finally, the results of this study suggest once more that there is no significant relationship between country-specific divorce risk and BMI among married individuals in Europe.
Gesehen am 24.05.2018